Controlling chromium slag pollution utilising scavengers: A case of Shandong Province, China. Issue 4 (April 2015) - Liu, Changhao; Côté, Raymond P
The problem of chromium slag pollution is a great challenge for China. It is now an urgent task for China to take effective measures to eliminate chromium slag pollution. This article examines the case of the treatment of chromium slag in Shandong Province and explores how chromium slag pollution can be eliminated in Shandong Province. It shows that the chromium slag stockpiled by the chemical plants was successfully utilised by local steel companies, who act as 'scavenger companies'. The driving mechanism, seeking a potential 'scavenger company' within the local region and the role of the local government on the case of Shandong Province are discussed. This article concludes that local steel companies can be utilised to effectively and efficiently treat the chromium slag while benefiting the steel companies. The local governments need to play multiple roles in solving the problem of chromium slag pollution. Seeking and identifying 'scavenger companies' within a region could be an important approach to reducing pollution within the region.